Integrated influence of soil tillage, nitrogen–potassium fertiliser and mulching on pineapple (Ananas comosus (L.) Merr.) growth and yield - Sossa, Elvire L; AGBANGBA, Codjo Emile; AMADJI, G. L.; AGBOSSOU, KOSSI EULOGE; Hounhouigan, Djidjoho J (My University, 2019)
Pineapple is one of the most important fruit in the world and its production requires appropiate cultural practices. This work aimed to investigate the influences of soil tillage, nitrogen–potassium (N-K) fertiliser and mulching on pineapple growth and yield. The experimental design was a split-split plot with four replications. The main factor was soil tillage (at two levels: flat tillage and ridging), the subplot factor was N-K fertilisation (at five levels: 1.6 N and 1.6 K, 5.8 N and 6.6 K, 10 N and 11.6 K, 1.6 N and 11.6 K, and 10 N and 1.6 K, in g plant ) and the sub-subplot factor was use of fresh pineapple residues (at three levels: surface mulching (at 10 t ha-1), 10 t ha buried residues at 10 cm depth, and no mulching). Growth and yield parameters were recorded. A mixed ANOVA model was performed on ‘D’ leaf characteristics, biomass production and yield. The results suggested that soil ridging and burying of 1 kg m² of crop residues improved pineapple growth and yield. Nitrogen–potassium combinations 10 N and 11.6 K, 1.6 N and 11.6 K, and 5.8 N and 6.6 K (in g plant-1 ) resulted in better plant development and higher yield.
Keywords: buried residues; fertilisation; pineapple; ridging